2022
DOI: 10.1155/2022/4446243
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Resection Improved the Outcome of Intrahepatic Cholangiocarcinoma: A Propensity Score Matching Analysis of a Retrospective Cohort

Abstract: Background. Intrahepatic cholangiocarcinoma (ICC) is the second most common liver malignancy after hepatocellular carcinoma (HCC), with a dismal prognosis and high heterogeneity. The oncological advantages of anatomical resection (AR) and nonanatomical resection (NAR) in HCC have been studied, but surgical strategies for ICC remain controversial with insufficient investigations. Materials and Methods. From Jan 2013 to Dec 2016, 3880 consecutive patients were retrospectively reviewed from a single center. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Similarly, anatomic liver resection should be preferred in cases of iCCA in which the future liver remnant is sufficient. Hence, as reported in two recent large Chinese studies [34,35], this approach showed advantages in terms of OS and DFS, as well as no differences in the post-operative complications rate, compared to non-anatomical resection.…”
Section: Anatomical Vs Non-anatomical Liver Resectionsupporting
confidence: 66%
“…Similarly, anatomic liver resection should be preferred in cases of iCCA in which the future liver remnant is sufficient. Hence, as reported in two recent large Chinese studies [34,35], this approach showed advantages in terms of OS and DFS, as well as no differences in the post-operative complications rate, compared to non-anatomical resection.…”
Section: Anatomical Vs Non-anatomical Liver Resectionsupporting
confidence: 66%
“…The oncological advantage of ALR is confirmed in another recent, large, Chinese single-centre experience on 3,880 patients (30). The results demonstrate that AR improved long-term survival in terms of 1-, 3-and 5-year OS (70%, 46% and 34%, respectively) and a DFS (61%; 21%and 10%, respectively) with a statistical significance after PSM analysis.…”
Section: Anatomical Vs Non-anatomical Liver Resectionmentioning
confidence: 53%
“…A comprehensive literature search was conducted in databases including PubMed, Embase, the Cochrane Library, Medline, and Web of Science to identify relevant studies evaluating the potential benefits of AR for ICC patients. Ultimately, as presented in Supplementary Table 3 , a total of six studies encompassing 1523 patients were included in the analysis [ 13 , 14 , 19 , 31 – 33 ], with 764 patients allocated to the AR group and 759 patients allocated to the NAR group. The findings from five studies collectively indicated a favorable effect of AR on the prognosis of ICC, along with reduced rates of postoperative recurrence [ 13 , 14 , 31 – 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, as presented in Supplementary Table 3 , a total of six studies encompassing 1523 patients were included in the analysis [ 13 , 14 , 19 , 31 – 33 ], with 764 patients allocated to the AR group and 759 patients allocated to the NAR group. The findings from five studies collectively indicated a favorable effect of AR on the prognosis of ICC, along with reduced rates of postoperative recurrence [ 13 , 14 , 31 – 33 ]. Conversely, the outcomes of the remaining study indicated that the implementation of AR did not yield improvements in prognosis among patients with solitary ICC that lacked direct invasion of adjacent organs or extrahepatic metastases [ 19 ].…”
Section: Resultsmentioning
confidence: 99%